This Land is Your Land: Mapping Outdoor Recreation and Publicly Accessible Lands in Southern Wisconsin - Trainor, Clare; Little, Calla; Kowalsky, Katie; Howell, Megan (My University, 2016)
This project attempts to create an interactive web map of nature based recreational activities and publicly accessible lands in Southeastern and SouthCentral Wisconsin. Due to the lack of accessible information, we felt there was a need to build an interface that synthesized data from multiple sources, with the goal of informing the public about the types of publicly accessible lands and the variety of recreational opportunities in the study area. This map leverages open source mapping software such as jQuery, Leaflet, Bootstrap and Mapbox tiles in its creation. While we created a successful web map, our struggles with collecting and formatting geographic data reflect the poor quality currently available to the public. The process of this project shows the potential for future mapping endeavours of other public services in the state of Wisconsin.
Includes maps, tables, appendices, bibliography
Keywords: Recreation; Outdoor; Accessible land; Public; Southern Wisconsin